Regime‐dependent effects of uncertainty on inflation and output growth: evidence from the United Kingdom and the United States. (18th January 2018) - Chowdhury, Kushal Banik; Kundu, Srikanta; Sarkar, Nityananda
Abstract: Employing a bivariate regime switching model, this paper attempts to examine the regime‐dependent effects of inflation uncertainty and output growth uncertainty on inflation and output growth. Using monthly data of the United Kingdom and the United States, we provide evidence that both nominal and real uncertainty exert regime‐dependent impacts on inflation. Furthermore, in case of both the countries, inflation uncertainty has adverse impact on output growth mainly during the period of economic contraction. Also, for these two countries, it can be argued that higher real uncertainty significantly reduces output growth only in their respective low output growth regimes.